Full-temperature-range polymer-based solid electrolyte, solid-state battery and preparation method
By optimizing the ratio of polymer monomers and plasticizers and in-situ polymerization process, polymer-based solid electrolytes with soft long side chains were prepared, which solved the stability and conductivity of polymer-based solid-state batteries in the full temperature domain. Problem, high-efficiency electrochemical performance at extreme temperatures is achieved.
Patent Information
- Application Number
- CN202411615335.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-21
AI Technical Summary
Existing polymer-based solid-state batteries are hindered ion transport at low temperatures and insufficient electrolyte stability at high temperatures, which cannot meet the needs of the full temperature domain.
By screening polymer monomers and plasticizers, optimizing the precursor ratio, a polymer-based solid electrolyte with soft long side chains was prepared by in-situ polymerization process to improve its thermal stability and low-temperature conductivity.
It has achieved good physical and chemical properties and electrochemical properties in the full temperature domain of -40-70℃, solved the problems of impeded low-temperature ion transport and insufficient stability of high-temperature electrolytes, and is suitable for lithium batteries and sodium batteries.
Smart Images

Figure CN119490607A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a full-temperature range polymer-based solid electrolyte, a solid-state battery and a preparation method thereof. Background Art
[0002] With the rapid growth of high-performance demands for electric vehicles, energy storage devices, etc., the application scope of lithium batteries is becoming more and more extensive, and the application environment is becoming increasingly complex and diverse. However, the current carbonate-based electrolytes cannot meet the use requirements of lithium batteries under harsh working conditions. Because their voltage window is limited to 4.3V, the operating temperature range is narrow (-20℃—+50℃), and they are easy to burn. At the same time, liquid carbonate-based electrolytes inevitably undergo parasitic reactions with metallic lithium, and the growth of lithium dendrites on the lithium negative electrode may pose a safety risk and ultimately damage the battery.
[0003] Solid electrolytes are non-volatile, flame-retardant, and stable with metallic lithium. Therefore, the development of solid-state lithium batteries using solid electrolytes can effectively solve the problems of energy density and safety. Among the currently developed solid electrolytes, polymer electrolytes are considered the most promising materials for preparing solid-state batteries due to their good flexibility, close contact with electrodes, easy processing, and low cost. However, polymer electrolytes (for example, electrolytes based on polyethylene oxide (PEO)) cannot achieve stable operation of solid-state batteries from low temperature (<-20°C) to high temperature (>+60°C), and the problem is further amplified in the case of fast charging. This is because the ionic conductivity of polymer electrolytes is low, and Li + The transport kinetics are slow, the lithium deposition is uneven, and once the temperature drops below the glass transition temperature, the polymer relaxation becomes very slow, and the ionic conductivity of the electrolyte is greatly reduced, even close to zero. + The transmission rate is faster, but polymer-based solid-state batteries are more likely to fail. As the temperature rises, the side reactions between the electrolyte and the electrode become more intense, the electrode / electrolyte interface film gradually thickens, and the "formation-degradation-reconstruction" process is repeated, and gas production intensifies. At the same time, high temperature will also reduce the mechanical strength of the polymer electrolyte, accelerate the aging rate of the electrolyte, and lead to short-circuit risks such as direct contact between the positive and negative electrodes and dendrite growth.
[0004] Therefore, there is an urgent need to design a polymer-based solid electrolyte that meets the requirements of fast ion conduction at low temperatures, stable electrolyte-electrode interface at high temperatures, and suitable for the entire temperature range. Summary of the invention
[0005] The purpose of the present invention is to provide a full-temperature range polymer-based solid electrolyte, solid-state battery and preparation method to address the technical problems of existing polymer-based electrolytes such as obstructed ion transmission at low temperatures (<-20°C) and insufficient electrolyte stability at high temperatures (>+60°C), so as to prepare full-temperature range polymer-based solid electrolytes and solid-state batteries with an operating temperature of -40-70°C.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a full-temperature range polymer-based solid electrolyte, comprising:
[0007] The preparation method comprises:
[0008] The alkali metal salt, the polymer monomer and the plasticizer are mixed uniformly in proportion to obtain an electrolyte precursor; wherein the polymer monomer includes: a fluorinated acrylate compound; the plasticizer includes: one or more of a fluorinated carboxylic acid ester compound, a fluorinated carbonate compound or a fluorinated amide compound;
[0009] An initiator is added to the electrolyte precursor, and the mixture is heated and polymerized to obtain a polymer-based solid electrolyte having polar functional groups that form dipole groups, namely the full-temperature range polymer-based solid electrolyte.
[0010] Preferably, in the electrolyte precursor, the mass ratio of the polymer monomer to the plasticizer is 1:10-10:1; and the concentration of the alkali metal salt in the electrolyte precursor is 0.5 mol / L-2 mol / L.
[0011] Preferably, the mass of the initiator is less than or equal to 1% of the mass of the electrolyte precursor;
[0012] The heating conditions for the thermal polymerization are: heating at 45-80° C. for 0.05-24 h.
[0013] Preferably, the alkali metal salt includes one or more of lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium hexafluorophosphate, sodium perchlorate, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide;
[0014] The fluorinated acrylate compound includes one or more of trifluoroethyl acrylate, hexafluoroisopropyl acrylate, pentafluoropropyl acrylate, hexafluorobutyl acrylate, heptafluorobutyl acrylate, heptafluoroisobutyl acrylate, nonafluoropentyl acrylate, tridecafluorooctyl acrylate and dodecafluoroheptyl methacrylate;
[0015] The fluorinated carboxylic acid ester compound includes one or more of: methyl trifluoropropionate, methyl difluoroacetate, methyl tetrafluoropropionate, ethyl difluoroacetate, and ethyl trifluoropropionate;
[0016] The fluorinated carbonate compounds include: trifluoropropylene carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate, methyl trifluoroethyl carbonate, tetrafluoropropyl methyl carbonate, one or more thereof;
[0017] The fluorinated amide compounds include: one or more of N,N-diethyl-2,3,3,3-tetrafluoropropionamide, 2,2,2-trifluoro-N,N-dimethylacetamide, and 2,3,3,3-tetrafluoropropionamide.
[0018] Preferably, the polar functional group forming the dipole group includes one or more of a carbonyl group (C=O), an ether bond (COC) and a fluorinated group (-F).
[0019] In a second aspect, an embodiment of the present invention provides a full-temperature range polymer-based solid electrolyte prepared by the preparation method described in the first aspect above.
[0020] Preferably, the working environment temperature of the full-temperature range polymer-based solid electrolyte is -40-70°C.
[0021] In a third aspect, an embodiment of the present invention provides a solid-state battery, comprising the full-temperature range polymer-based solid electrolyte described in the second aspect above.
[0022] Preferably, the positive electrode active material of the solid-state battery includes: one or more of a layered oxide, a polyanionic compound or a Prussian blue compound;
[0023] The layered oxide includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and sodium nickel iron manganese oxide;
[0024] The polyanionic compound includes: lithium iron phosphate and / or sodium vanadium phosphate;
[0025] The Prussian blue compounds include: Prussian white;
[0026] The negative electrode active material includes: one of graphite, metal lithium sheet and sodium sheet.
[0027] In a fourth aspect, an embodiment of the present invention provides a method for preparing the solid-state battery according to the third aspect, comprising:
[0028] After the polymer monomer and the plasticizer are uniformly mixed in proportion, an alkali metal salt is added, and after the mixture is completely dissolved, an electrolyte precursor is obtained; an initiator is added to the electrolyte precursor to obtain a liquid precursor to be polymerized; wherein the polymer monomer includes: a fluorinated acrylate compound; the plasticizer includes: one or more of a fluorinated carboxylic acid ester compound, a fluorinated carbonate compound or a fluorinated amide compound;
[0029] Injecting the liquid precursor to be polymerized between the positive and negative electrodes inside the battery, so that the liquid precursor to be polymerized fully infiltrates the positive and negative electrodes and the separator of the battery, and then completing the packaging of the battery; or, dripping the liquid precursor to be polymerized onto the positive electrode, the separator and the negative electrode, and then completing the battery assembly;
[0030] The battery is polymerized under heating conditions to obtain the solid-state battery.
[0031] The preparation method of the full-temperature polymer-based solid electrolyte provided by the embodiment of the present invention is to prepare a polymer-based solid electrolyte suitable for the full temperature range by screening polymer monomers and plasticizers, optimizing the precursor ratio, and using an in-situ polymerization process. By using polymer monomers with soft long side chains, the plasticizer molecules can be effectively anchored between polymer chains, reducing the leakage of plasticizer molecules, and effectively improving the thermal stability of the electrolyte; at the same time, the parasitic reaction between the plasticizer molecules and the electrodes is reduced, so that the solid-state battery can work stably at high temperatures (>+60°C); after the polymer monomers are polymerized, a solid electrolyte containing polar groups is formed. Because the polar functional groups have high electronegativity, the interaction between the formed dipoles and the alkali metal ions enables the ions to be quickly decoupled from the polymer matrix, reducing the obstruction of ion transmission, and helping to improve the conductivity at low temperatures (<-20°C); in addition, the flexible structure plasticizer with long side chains has good intermolecular freedom at low temperatures, which can further reduce the obstacles to ion migration, so that the electrolyte can also maintain a high ionic conductivity at low temperatures. The full-temperature range polymer-based solid electrolyte prepared by the present invention exhibits good physical and chemical properties and electrochemical performances at an operating environment temperature of -40-70°C, and can be extended from lithium batteries to sodium batteries, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A flow chart of a method for preparing a full-temperature range polymer-based solid electrolyte provided by an embodiment of the present invention;
[0033] Figure 2 1 / T curve of the ionic conductivity of the polymer-based solid electrolyte prepared in Example 1 of the present invention;
[0034] Figure 3 is the thermal stability curve of the polymer-based solid electrolyte in Example 1 of the present invention;
[0035] Figure 4 The electrochemical window curve of the polymer-based solid electrolyte tested by voltammetry in Example 2 of the present invention;
[0036] Figure 5This is a battery performance diagram of a solid-state battery assembled with a polymer-based solid electrolyte, an NCM811 positive electrode, and a lithium metal negative electrode at -40°C to 70°C prepared in Example 2 of the present invention;
[0037] Figure 6 This is a battery performance diagram of a solid-state battery assembled with a polymer-based solid electrolyte prepared in Example 2 of the present invention, an NVP positive electrode, and a sodium metal negative electrode at -40°C to 70°C. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0039] Embodiments of the present invention provide a full-temperature range polymer-based solid electrolyte, a solid-state battery, and a preparation method.
[0040] First, the preparation method of the full-temperature range polymer-based solid electrolyte is described. Figure 1 The flow chart of the preparation method of the full-temperature range polymer-based solid electrolyte provided by the embodiment of the present invention is as follows: Figure 1 As shown, the preparation method of the full-temperature range polymer-based solid electrolyte mainly includes the following steps:
[0041] Step 110, the alkali metal salt, the polymer monomer, and the plasticizer are mixed evenly according to a certain proportion to obtain an electrolyte precursor.
[0042] Among them, the alkali metal salt can be a lithium salt or a sodium salt; the alkali metal salt preferably includes: lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium hexafluorophosphate and sodium perchlorate, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide or one or more thereof.
[0043] The polymer monomers include: fluorinated acrylate compounds; the fluorinated acrylate compounds preferably include: one or more of trifluoroethyl acrylate, hexafluoroisopropyl acrylate, pentafluoropropyl acrylate, hexafluorobutyl acrylate, heptafluorobutyl acrylate, heptafluoroisobutyl acrylate, nonafluoropentyl acrylate, tridecafluorooctyl acrylate and dodecafluoroheptyl methacrylate.
[0044] Plasticizers include: one or more of fluorinated carboxylic acid ester compounds, fluorinated carbonate compounds or fluorinated amide compounds. Among them, fluorinated carboxylic acid ester compounds include: one or more of methyl trifluoropropionate, methyl difluoroacetate, methyl tetrafluoropropionate, ethyl difluoroacetate, ethyl trifluoropropionate; fluorinated carbonate compounds include: one or more of trifluoropropylene carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate, methyl trifluoroethyl carbonate, tetrafluoropropyl methyl carbonate; fluorinated amide compounds include: one or more of N,N-diethyl-2,3,3,3-tetrafluoropropionamide, 2,2,2-trifluoro-N,N-dimethylacetamide, 2,3,3,3-tetrafluoropropionamide.
[0045] In the electrolyte precursor, the mass ratio of the polymer monomer to the plasticizer is 1:10-10:1, more preferably 1:5-1:1; the concentration of the alkali metal salt in the electrolyte precursor is 0.5 mol / L-2 mol / L.
[0046] Optionally, functional additives such as fluoroethylene carbonate (FEC), fluoropropylene carbonate (FPC), fluoromethyl carbonate (FMC), ethylene carbonate (EC) or allyl sulfite (AES) may be added to the electrolyte precursor to help form an interface protection layer and improve interface stability.
[0047] Step 120, adding an initiator to the electrolyte precursor, heating and polymerizing, and obtaining a polymer-based solid electrolyte having polar functional groups that form dipole groups, that is, a full-temperature range polymer-based solid electrolyte.
[0048] Wherein, the mass of the initiator is less than or equal to 1% of the mass of the electrolyte precursor;
[0049] The heating conditions for thermal polymerization are: heating at 45-80°C for 0.05-24h.
[0050] Preferably, the initiator used in the present invention includes: azobisisobutyronitrile (AI BN) or azobisisobutyltetrazole (ABCN).
[0051] The present invention prepares a polymer-based solid electrolyte applicable to the entire temperature range by screening polymer monomers and plasticizers, optimizing the precursor ratio, and utilizing an in-situ polymerization process.
[0052] By using polymer monomers with soft long side chains, the plasticizer molecules are anchored between polymer chains, the leakage of plasticizer molecules is reduced, and the thermal stability of the electrolyte is effectively improved; at the same time, the parasitic reaction between the plasticizer molecules and the electrode is reduced, the interface stability of the electrolyte in a high temperature environment is improved, and the solid-state battery can work stably at high temperatures (>+60°C); the present invention mainly uses fluorinated carboxylic acid ester compounds, fluorinated carbonate compounds or fluorinated amide compounds as plasticizers. These compounds have good ionic conductivity, can withstand high voltage, and can improve the electrode / electrolyte interface performance. After addition, the polymer-based electrolyte exhibits good oxidation resistance, and the electrochemical window is widened to about 5.2V, which can match the high-voltage positive electrode material and maintain the chemical stability of the interface, thereby ensuring safety and stability under high temperature conditions, and realizing a high-safety, high-specific energy solid-state battery.
[0053] After polymerization, the polymer monomer forms a solid electrolyte containing polar groups. Since the polar functional groups have high electronegativity, the interaction between the formed dipole and the alkali metal ions enables the ions to be quickly decoupled from the polymer matrix, reducing the obstruction of ion transmission, and helping to improve the conductivity at low temperatures (<-20°C). In the present invention, the dipole mainly comes from the polymer monomer used. After polymerization, the polymer monomer forms a polymer skeleton containing polar groups. Taking fluorinated acrylate compounds as an example, the polar groups include the following main components: 1. Carbonyl (C=O): Fluorinated acrylate compounds usually contain carbonyl (C=O), which is polar. After polymerization, these polar groups are retained in the polymer structure; in the carbonyl group, the carbon atom and the oxygen atom are connected by a double bond, and the electronegativity of oxygen is significantly higher than that of carbon, so oxygen will attract more electron density, causing the electron cloud to shift toward oxygen, so that oxygen carries a partial negative charge, while carbon carries a partial positive charge, forming a dipole; 2. Ether bond (COC): In the ether bond, the oxygen atom is located between two carbon atoms, Oxygen has a high electronegativity, so oxygen attracts the surrounding electron density. Therefore, oxygen carries a partial negative charge, while the carbon connected to oxygen carries a partial positive charge, thereby forming a dipole in the COC bond; 3. Fluorinated group (-F): The fluorine atom itself has a high electronegativity. After polymerization, the fluorinated acrylate retains the structure with fluorinated groups. These groups provide a significant dipole effect, making the polymer as a whole highly polar. For example, when fluorine forms a covalent bond with atoms such as carbon (such as a CF bond), fluorine strongly attracts electrons in the covalent bond, making the fluorine end carry a partial negative charge, while the carbon end carries a partial positive charge, forming a strong dipole. After the polymerization reaction, these dipoles are distributed in the polymer chain of the solid electrolyte, interacting with ions and promoting ion conduction.
[0054] The full-temperature range polymer-based solid electrolyte prepared by the present invention exhibits good physical and chemical properties and electrochemical performances at an operating environment temperature of -40-70°C, and can be extended from lithium batteries to sodium batteries, and has good application prospects.
[0055] When it is applied to lithium solid-state batteries or sodium solid-state batteries, the solid-state batteries can be prepared as follows:
[0056] Step 210, after the polymer monomer and the plasticizer are uniformly mixed in proportion, an alkali metal salt is added, and after the salt is completely dissolved, an electrolyte precursor is obtained; an initiator is added to the electrolyte precursor to obtain a liquid precursor to be polymerized;
[0057] Among them, the materials are the same as those used in the preparation of the above-mentioned polymer-based solid electrolyte, and will not be described in detail.
[0058] Step 220, injecting the liquid precursor to be polymerized between the positive and negative electrodes inside the battery, so that the liquid precursor to be polymerized fully infiltrates the positive and negative electrodes and the separator of the battery, and then completing the packaging of the battery; or, dripping the liquid precursor to be polymerized onto the positive electrode, the separator and the negative electrode, and then completing the battery assembly;
[0059] Step 230, initiating polymerization of the battery under heating conditions to obtain a solid-state battery.
[0060] Those skilled in the art can refer to the following materials to select the positive and negative electrode materials for solid-state batteries as needed.
[0061] The positive electrode active materials of the solid-state battery include: one or more of layered oxides, polyanionic compounds or Prussian blue compounds; wherein the layered oxides include: one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, sodium nickel iron manganese oxide; the polyanionic compounds include: lithium iron phosphate and / or sodium vanadium phosphate; the Prussian blue compounds include: Prussian white; the negative electrode active materials include: one of graphite, metal lithium sheets, and sodium sheets.
[0062] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] Example 1
[0064] This embodiment prepares a full-temperature range polymer-based solid electrolyte.
[0065] Preparation of electrolyte precursor: The polymer monomer butyl hexafluoroacrylate (HFA) and the plasticizer methyl trifluoropropionate (MTFP) are mixed in a mass ratio of 1:3, and then 10wt% of the additive fluoroethylene carbonate (FEC) is added and stirred at 30°C for about 2h; then 1mol / L of lithium bis(fluorosulfonyl)imide (LiFSI) is added and stirred at 30°C for about 2h until it is completely dissolved, and finally a uniformly mixed electrolyte precursor is obtained.
[0066] Preparation of polymer-based solid electrolyte: 1% by mass of azobisisobutyronitrile (AI BN) was added to the electrolyte precursor obtained above, and heated at 60° C. for 2 h to fully polymerize HFA to obtain a polymer-based solid electrolyte.
[0067] The polymer-based solid electrolyte was solidified in a sealed electrolytic cell to test the ionic conductivity: a 200 μm thick copper sheet was used as a double electrode, and the conductivity at each temperature was tested at -40-60°C with each 10°C test point. The results are shown in FIG. Figure 2 As shown in Figure 2, the conductivity increases with the increase of temperature, and the room temperature ionic conductivity of the obtained solid electrolyte is 2.95×10 -3 S cm -1 At -40℃, the ionic conductivity can reach 0.27×10 -4 S cm -1 At the same time, the thermogravimetric results are as follows Figure 3 As shown, the polymer-based solid electrolyte of this embodiment exhibits good thermal stability, and the thermal degradation temperature is increased to 155°C.
[0068] Example 2
[0069] This embodiment prepares a lithium solid-state battery containing a polymer-based solid electrolyte.
[0070] Preparation of electrolyte precursor: polymer monomer HFA and plasticizer MTFP are mixed in a mass ratio of 1:3, and then 10wt% of additive FEC is added and stirred at 30°C for about 2h. After mixing evenly; then 1mol / L LiFS I is added and stirred at 30°C for about 2h until completely dissolved to obtain an electrolyte precursor.
[0071] Preparation of polymer-based solid electrolyte and assembly of solid-state battery: 1% azobisisobutyronitrile (AIBN) was added to the electrolyte precursor obtained above to form a precursor solution; 15 μL of the obtained precursor solution was dropped on Li Ni 0.8 Co 0.1 Mn 0.1O2 (NCM811) positive electrode, and then cover it with a polypropylene diaphragm, and add 15μL of the precursor solution again to wet the diaphragm, and then stack the negative electrode metal lithium sheet, gasket, and shrapnel; finally, move the assembled battery to a heating device and heat it at 60°C for 2h to allow HFA to undergo polymerization to form a polymer-based solid electrolyte, and at the same time, form an integrated stack including a positive electrode, electrolyte, diaphragm, and negative electrode in situ, and finally encapsulate the battery in a shell to obtain a solid-state battery.
[0072] The NCM811 positive electrode described above was replaced with a stainless steel gasket, and the Li||SS battery for testing in this embodiment was assembled in the same manner as above, and a linear sweep voltammetry test (LSV) was performed. The electrochemical window of the polymer-based solid electrolyte in this embodiment was obtained by the test, as shown in FIG. Figure 4 It can be seen that the electrochemical window of the polymer-based solid electrolyte in this embodiment reaches 5.2V.
[0073] The electrochemical performance of the solid-state battery with NCM811 as the positive electrode was characterized. Figure 5 At -40℃, at a charge and discharge rate of 0.1C, the discharge capacity is 107mAh / g, which can maintain 48% of its room temperature capacity; at a high temperature of 70℃, it can work stably, and its discharge capacity is about 251mAh / g.
[0074] Example 3
[0075] This example prepares a sodium solid-state battery containing a polymer-based solid electrolyte.
[0076] Preparation of electrolyte precursor: polymer monomer HFA and plasticizer MTFP are mixed in a mass ratio of 1:3, and then 10wt% of additive FEC is added and stirred at 30°C for about 2h. After mixing evenly, 1mol / L of sodium bis(fluorosulfonyl)imide is added and stirred at 30°C for about 2h until completely dissolved to obtain an electrolyte precursor.
[0077] Preparation of polymer-based solid electrolyte and assembly of solid-state battery: add 1% by mass of azobisisobutyronitrile (AI BN) to the electrolyte precursor obtained above to form a precursor solution; take 15 μL of the obtained precursor solution, drop it on the sodium vanadium phosphate (NVP) positive electrode, then cover it with a polypropylene diaphragm, and add 15 μL of the precursor solution again to wet the diaphragm, and then stack the negative electrode metal lithium sheet, gasket, and shrapnel; finally, move the assembled battery to a heating device and heat it at 60°C for 2h to allow HFA to undergo a polymerization reaction to form a polymer-based solid electrolyte, and at the same time, form an integrated stack including a positive electrode, an electrolyte, a diaphragm and a negative electrode in situ, and finally package the battery in a shell to obtain a solid-state battery.
[0078] The electrochemical performance of the solid-state battery with NVP as the positive electrode was characterized. Figure 6 As shown. It can be seen that the solid-state battery can still work stably at -40℃-70℃, showing good temperature adaptability.
[0079] Example 4
[0080] This embodiment prepares a lithium solid-state battery containing a polymer-based solid electrolyte.
[0081] Preparation of electrolyte precursor: polymer monomer HFA and plasticizer MTFP are mixed in a mass ratio of 1:2, and then 10wt% of additive FEC is added and stirred at 30°C for about 2h. After mixing evenly, LiFS I is added at 2mol / L and stirred at 30°C for about 2h until completely dissolved to obtain an electrolyte precursor.
[0082] Preparation of polymer-based solid electrolyte and assembly of solid-state battery: add 1% by mass of azobisisobutyronitrile (AI BN) to the electrolyte precursor obtained above to form a precursor solution; take 15 μL of the obtained precursor solution, drop it on the NCM811 positive electrode, then cover it with a polypropylene diaphragm, and add 15 μL of the precursor solution again to wet the diaphragm, and then stack the negative electrode metal lithium sheet, gasket, and shrapnel; finally, move the assembled battery to a heating device and heat it at 60°C for 2h to allow HFA to undergo a polymerization reaction to form a polymer-based solid electrolyte, and at the same time, form an integrated stack including a positive electrode, an electrolyte, a diaphragm and a negative electrode in situ, and finally package the battery in a shell to obtain a solid-state battery.
[0083] At -40°C and a charge and discharge rate of 0.1C, the solid-state battery has a discharge capacity of 45 mAh / g and can maintain 20% of its room temperature capacity. At a high temperature of 70°C, it can work stably with a discharge capacity of about 235 mAh / g.
[0084] Example 5
[0085] This embodiment prepares a lithium solid-state battery containing a polymer-based solid electrolyte.
[0086] Preparation of electrolyte precursor: polymer monomer HFA and plasticizer MTFP are mixed in a mass ratio of 1:1, and then 10wt% of additive FEC is added and stirred at 30°C for about 2h. After mixing evenly, LiFS I is added at 2mol / L and stirred at 30°C for about 2h until completely dissolved to obtain an electrolyte precursor.
[0087] Preparation of polymer-based solid electrolyte and assembly of solid-state battery: add 1% by mass of azobisisobutyronitrile (AI BN) to the electrolyte precursor obtained above to form a precursor solution; take 15 μL of the obtained precursor solution, drop it on the NCM811 positive electrode, then cover it with a polypropylene diaphragm, and add 15 μL of the precursor solution again to wet the diaphragm, and then stack the negative electrode metal lithium sheet, gasket, and shrapnel; finally, move the assembled battery to a heating device and heat it at 60°C for 2h to allow HFA to undergo a polymerization reaction to form a polymer-based solid electrolyte, and at the same time, form an integrated stack including a positive electrode, an electrolyte, a diaphragm and a negative electrode in situ, and finally package the battery in a shell to obtain a solid-state battery.
[0088] At -40°C and a charge and discharge rate of 0.1C, the solid-state battery has a discharge capacity of 20mAh / g, which can maintain 9% of its room temperature capacity. At a high temperature of 70°C, it can work stably with a discharge capacity of about 220mAh / g.
[0089] Example 6
[0090] This embodiment prepares a lithium solid-state battery containing a polymer-based solid electrolyte.
[0091] Preparation of electrolyte precursor: polymer monomer trifluoroethyl acrylate and plasticizer fluoroethylene carbonate are mixed in a mass ratio of 1:5, and then 10wt% of additive FEC is added and stirred at 30°C for about 2h. After mixing evenly, 2mol / L of lithium difluorooxalate borate is added and stirred at 30°C for about 2h until completely dissolved to obtain an electrolyte precursor.
[0092] Preparation of polymer-based solid electrolyte and assembly of solid-state battery: add 0.5% by mass of azobisisobutyronitrile (AI BN) to the electrolyte precursor obtained above to form a precursor solution; take 15 μL of the obtained precursor solution, drop it on the lithium cobalt oxide positive electrode, then cover it with a polypropylene diaphragm, and add 15 μL of the precursor solution again to wet the diaphragm, and then stack the negative electrode metal lithium sheet, gasket, and shrapnel; finally, move the assembled battery to a heating device and heat it at 45°C for 8h to cause trifluoroethyl acrylate to undergo polymerization to form a polymer-based solid electrolyte, and at the same time, form an integrated stack including a positive electrode, an electrolyte, a diaphragm and a negative electrode in situ, and finally package the battery in a shell to obtain a solid-state battery.
[0093] Example 7
[0094] This embodiment prepares a lithium solid-state battery containing a polymer-based solid electrolyte.
[0095] Preparation of electrolyte precursor: The polymer monomer 13fluorooctyl acrylate and the plasticizer N,N-diethyl-2,3,3,3-tetrafluoropropionamide are mixed in a mass ratio of 2:5, and then 10wt% of the additive FEC is added and stirred at 30°C for about 2h. After mixing evenly, 0.5mol / L of lithium difluorobis(oxalyl)phosphate is added and stirred at 30°C for about 2h until it is completely dissolved to obtain an electrolyte precursor.
[0096] Preparation of polymer-based solid electrolyte and assembly of solid-state battery: add 0.2% by mass of azobisisobutyronitrile (AI BN) to the electrolyte precursor obtained above to form a precursor solution; take 15 μL of the obtained precursor solution, drip it on the lithium cobalt oxide positive electrode, then cover it with a polypropylene diaphragm, and drip 15 μL of the precursor solution again to wet the diaphragm, and then stack the negative electrode metal lithium sheet, gasket, and shrapnel; finally, move the assembled battery to a heating device and heat it at 80°C for 2h to polymerize acrylate to form a polymer-based solid electrolyte, and at the same time form an integrated stack including a positive electrode, an electrolyte, a diaphragm and a negative electrode in situ, and finally encapsulate the battery in a shell to obtain a solid-state battery.
[0097] The present invention prepares a polymer-based solid electrolyte applicable to the entire temperature range by screening polymer monomers and plasticizers, optimizing the precursor ratio, and using an in-situ polymerization process. The full-temperature range polymer-based solid electrolyte prepared by the present invention exhibits good physical and chemical properties and electrochemical performance at an operating ambient temperature of -40-70°C, can be applied to lithium batteries and sodium batteries, and has good application prospects.
[0098] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a full-temperature range polymer-based solid electrolyte, characterized in that: The preparation method comprises: The alkali metal salt, the polymer monomer and the plasticizer are mixed uniformly in proportion to obtain an electrolyte precursor; wherein the polymer monomer includes: a fluorinated acrylate compound; the plasticizer includes: one or more of a fluorinated carboxylic acid ester compound, a fluorinated carbonate compound or a fluorinated amide compound; An initiator is added to the electrolyte precursor, and the mixture is heated and polymerized to obtain a polymer-based solid electrolyte having polar functional groups that form dipole groups, namely the full-temperature range polymer-based solid electrolyte.
2. The preparation method according to claim 1, characterized in that: In the electrolyte precursor, the mass ratio of the polymer monomer to the plasticizer is 1:10-10:1; and the concentration of the alkali metal salt in the electrolyte precursor is 0.5 mol / L-2 mol / L.
3. The preparation method according to claim 1, characterized in that: The mass of the initiator is less than or equal to 1% of the mass of the electrolyte precursor; The heating conditions for the thermal polymerization are: heating at 45-80° C. for 0.05-24 h.
4. The preparation method according to claim 1, characterized in that: The alkali metal salt includes one or more of lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium hexafluorophosphate, sodium perchlorate, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; The fluorinated acrylate compound includes one or more of trifluoroethyl acrylate, hexafluoroisopropyl acrylate, pentafluoropropyl acrylate, hexafluorobutyl acrylate, heptafluorobutyl acrylate, heptafluoroisobutyl acrylate, nonafluoropentyl acrylate, tridecafluorooctyl acrylate and dodecafluoroheptyl methacrylate; The fluorinated carboxylic acid ester compound includes one or more of: methyl trifluoropropionate, methyl difluoroacetate, methyl tetrafluoropropionate, ethyl difluoroacetate, and ethyl trifluoropropionate; The fluorinated carbonate compounds include: trifluoropropylene carbonate, fluoroethylene carbonate, bisfluoroethylene carbonate, methyl trifluoroethyl carbonate, tetrafluoropropyl methyl carbonate, one or more thereof; The fluorinated amide compounds include: one or more of N,N-diethyl-2,3,3,3-tetrafluoropropionamide, 2,2,2-trifluoro-N,N-dimethylacetamide, and 2,3,3,3-tetrafluoropropionamide.
5. The preparation method according to claim 1, characterized in that: The polar functional groups forming dipole groups include: one or more of carbonyl groups (C=O), ether bonds (COC) and fluorinated groups (-F).
6. A full-temperature range polymer-based solid electrolyte prepared by the preparation method described in any one of claims 1 to 5.
7. The full-temperature range polymer-based solid electrolyte according to claim 6, characterized in that: The working environment temperature of the full-temperature range polymer-based solid electrolyte is -40-70°C.
8. A solid-state battery, characterized in that: The solid-state battery comprises the full-temperature range polymer-based solid electrolyte as described in claim 6 above.
9. The solid-state battery according to claim 8, characterized in that: The positive electrode active material of the solid-state battery includes: one or more of a layered structure oxide, a polyanion compound or a Prussian blue compound; The layered oxide includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, and sodium nickel iron manganese oxide; The polyanionic compound includes: lithium iron phosphate and / or sodium vanadium phosphate; The Prussian blue compounds include: Prussian white; The negative electrode active material includes: one of graphite, metal lithium sheet and sodium sheet.
10. A method for preparing a solid-state battery according to claim 8, characterized in that: The preparation method comprises: After the polymer monomer and the plasticizer are uniformly mixed in proportion, an alkali metal salt is added, and after the mixture is completely dissolved, an electrolyte precursor is obtained; an initiator is added to the electrolyte precursor to obtain a liquid precursor to be polymerized; wherein the polymer monomer includes: a fluorinated acrylate compound; the plasticizer includes: one or more of a fluorinated carboxylic acid ester compound, a fluorinated carbonate compound or a fluorinated amide compound; Injecting the liquid precursor to be polymerized between the positive and negative electrodes inside the battery, so that the liquid precursor to be polymerized fully infiltrates the positive and negative electrodes and the separator of the battery, and then completing the packaging of the battery; or, dripping the liquid precursor to be polymerized onto the positive electrode, the separator and the negative electrode, and then completing the battery assembly; The battery is polymerized under heating conditions to obtain the solid-state battery.
Citation Information
Patent Citations
Electrolyte for rechargeable lithium battery and rechargeable lithium battery including same
CN103682438A
Copolymerization solid electrolyte, preparation method thereof and solid polymer lithium battery
CN114024025A
Semi-solid electrolyte, synthetic method and application thereof, and semi-solid lithium battery
CN116014238A
Preparation method of polymer solid electrolyte, solid electrolyte and solid battery
CN117229447A
High-voltage-resistant solid-state battery and preparation method thereof
CN117712499A
Cited By
Slow-release polymer coating as well as preparation method and application thereof
CN120682677A
Polymer electrolyte and preparation method and application thereof
CN120824418A
A polymer electrolyte, its preparation method and application
CN120824418B
Fluorinated acrylate reference solid electrolyte with hydrogen bond anchoring and amide dissociation as well as preparation method and application of fluorinated acrylate reference solid electrolyte
CN121076238A